Peningkatan Pengetahuan Ibu untuk Meningkatkan Produksi Asi dengan Pijat Oksitosin di PMB Sulistio Rahayu Lampung Tengah - Gangsar Indah Lestari; Prasetyowati Prasetyowati; Martini Martini; Yuliawatia Yuliawatia (Jurnal Mitrawarga, 2022)
Breast milk is the best food for babies, besides containing the nutrients needed by babies, it is also very much needed for growth and helps increase the baby's intelligence. The problem that often occurs in breastfeeding is the production process. Adequate milk production will be influenced by two things, namely direct and indirect factors. The direct factor is maternal health status, nutrition and hormone system, one of which affects the production of breast milk is the hormone oxytocin, besides influencing uterine contractions, it also provides positive feedback to the hypothalamus to stimulate prolactin which will produce breast milk, one way to stimulate oxytocin is by massage, which we know as Oxytocin Massage. Oxytocin massage is an acupressure technique used to stimulate milk production, but not all breastfeeding mothers know this technique. Mothers can get knowledge about breastfeeding from various activities in the community, one of which is the mother's class. Mother's classes are conducted by mothers during pregnancy, childbirth, postpartum and breastfeeding. Likewise, the Independent Midwife Practice (PMB) Sulistyo Rahayu has 25 members of the mother class, 15 of whom are nursing mothers. The increase in breast milk production with oxytocin massage can be seen from the results of research conducted by Cholifah (2014) which shows that there is an effect by performing acupressure technique with oxytocin massage, which significantly increases breast milk production with a p value <0.05. This is in accordance with the opinion of Susilowati (2018) the combination of oxytocin massage and breastcare on increasing breast milk production.